2020
DOI: 10.1101/2020.12.21.20248674
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pre-treatment clinical behavioral and blood leukocyte gene expression patterns predict rate of change in response to early intervention in autism

Abstract: Early detection and intervention are believed to be key to facilitating better outcomes in children with autism, yet the impact of age at treatment start on outcome is poorly understood. While clinical traits such as language ability have been shown to predict treatment outcome, whether or not and how information at the genomic level can predict treatment outcome is unknown. Leveraging a cohort of toddlers with autism who all received the same standardized intervention at a very young age and provided a blood … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Finally, we found multivariate leukocyte expression signatures can predict trajectories of response to early intervention treatment 52 , which underscores the mechanistic relevance of leukocytes to ASD and clinically important phenomena that can be individualized to specific patients.…”
Section: Discussionmentioning
confidence: 59%
“…Finally, we found multivariate leukocyte expression signatures can predict trajectories of response to early intervention treatment 52 , which underscores the mechanistic relevance of leukocytes to ASD and clinically important phenomena that can be individualized to specific patients.…”
Section: Discussionmentioning
confidence: 59%
“…Importantly, research shows that interventions delivered during the first 2 years of life lead to greater impact on developmental trajectories and symptom severity in comparison to interventions started later (4). In Lombardo et al 's study (4), children starting intervention during the first 24 months of age demonstrated predictable gains, while it was not the case for children starting intervention later.…”
Section: Introductionmentioning
confidence: 98%
“…Importantly, research shows that interventions delivered during the first 2 years of life lead to greater impact on developmental trajectories and symptom severity in comparison to interventions started later (4). In Lombardo et al 's study (4), children starting intervention during the first 24 months of age demonstrated predictable gains, while it was not the case for children starting intervention later. Moreover, in their recent study, Guthrie et al (5) showed that children starting a parent-mediated intervention, the Early Social Interaction (ESI) model, at 17 months of age, showed greater gains in receptive/expressive language, social communication, and daily living skills in comparison to children beginning the same intervention at 27 months of age.…”
Section: Introductionmentioning
confidence: 98%